2006
DOI: 10.1007/s10658-006-9054-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of downy mildew (Peronospora sparsa) in Rubus species using real-time PCR

Abstract: Downy mildew disease caused by Peronospora sparsa, also known as ÔdryberryÕ disease, is a serious threat to the cultivation of arctic bramble (Rubus arcticus) and boysenberry (Rubus spp. hybrid). A quantitative and sensitive screening method is necessary for the breeding of downy mildew resistant cultivars and for determining efficient disease control methods. A quantitative real-time PCR method using SYBR Ò Green I fluorescent dye was developed for the analysis of P. sparsa in arctic bramble, other Rubus spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…According to Rebollar-Alviter et al (2009), foliar symptoms are not always present, but the absence of these symptoms does not necessarily indicate the absence of disease in the fruit. Similar reports have been published in other growing areas of the world, such as New Zealand (Walter et al, 2014;personal communication); for this reason, diagnosis based on the absence of foliar symptoms is unreliable (Nordskog et al, 2003;Hukkanen et al, 2006Hukkanen et al, , 2008 and should not be the basis for disease management.…”
Section: Effect Of Treatments On the Foliar Disease Incidence And Sevsupporting
confidence: 57%
See 1 more Smart Citation
“…According to Rebollar-Alviter et al (2009), foliar symptoms are not always present, but the absence of these symptoms does not necessarily indicate the absence of disease in the fruit. Similar reports have been published in other growing areas of the world, such as New Zealand (Walter et al, 2014;personal communication); for this reason, diagnosis based on the absence of foliar symptoms is unreliable (Nordskog et al, 2003;Hukkanen et al, 2006Hukkanen et al, , 2008 and should not be the basis for disease management.…”
Section: Effect Of Treatments On the Foliar Disease Incidence And Sevsupporting
confidence: 57%
“…However, the lack of symptoms in the leaves does not indicate an absence of infection, as producers have had significant losses in asymptomatic plantings. Therefore, disease diagnosis based on the presence or absence of foliar symptoms is not a reliable technique for managing this disease (Hukkanen et al, 2006;Rebollar-Alviter et al, 2012). In this regard, different studies have shown that detection based on the Polymerase Chain Reaction (PCR), Real-time PCR and nested PCR using specific primers are more reliable techniques for the rapid and timely detection of the causal agent (Koponen et al, 2000;Hukkanen et al, 2008;RebollarAlviter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…El impacto es considerable, ya que genera pérdidas de producción entre el 50% y 70% (Rodríguez Díaz et al, 2017). Adicionalmente, el uso regular de fungicidas contribuye al desarrollo de cepas resistentes y de difícil control (Hukkanen et al, 2006).…”
Section: Introductionunclassified
“…Wang et al 2006;Pavon et al 2008) or in asymptomatic host tissue (e.g. Aegerter et al 2002;Hukkanan et al 2006). A particular field of interest is the identification of seed contamination with pathogenic oomycetes for which successful approaches have been published for the downy mildew pathogens of basil (Belbahri et al 2005) and sunflower (Thines et al 2004;Ioos et al 2007).…”
Section: Introductionmentioning
confidence: 99%